How to Manage in a Chinese Cultural Setting - Implications for TNCs - Ju, Shiyou (2007)
With the development of the Chinese economy, more and more foreign investors are attracted by its huge potential market. However, how to manage the company under a different culture background is still a difficult challenge for the expatriate managers. This dissertation aims to investigate the basic Chinese culture as well as it business characteristics under the cultural setting and give the TNCs useful recommendations.